Analyzing Sociopreneur Potency in Trenggalek Regency - Shanti Ike Wardani; Nunuk Latifah (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2021)
The rapid advancement of digitalization, along with an ever-shrinking pool of available jobs, needs people to think more productively as changes in the business world’s production methods accelerate. Social entrepreneurship is one strategy for overcoming society’s entrepreneurial problems, including financial constraints, managerial capabilities, limited networks, and a lack of government support. The purpose of this study is to ascertain and assess residents’ entrepreneurial motivations, social competency, and sociopreneur potential in Salamrejo Village, Karangan District, Trenggalek Regency. This study employed a quantitative approach in conjunction with explanatory research approaches. This study included 4812 individuals and randomly selected 98 samples. A closed questionnaire with a five Likert Scale was utilized to collect data in this investigation. Multiple linear regression analysis was performed on the data using the SPSS application. The findings of this study reveal that entrepreneurial motivation has a significant influence on sociopreneurs, whereas social competence has no significant effect on sociopreneurs. The study concludes that community entrepreneurship motivation is critical in building community excitement for developing a sociopreneur lifestyle that aspires to impact economic development.Keywords: Entrepreneurial Motivation, Social Competence, Sociopreneur